2010
DOI: 10.1007/s12116-009-9058-8
|View full text |Cite
|
Sign up to set email alerts
|

Patronage, District Creation, and Reform in Uganda

Abstract: The effects of economic and political reforms on patronage in Africa remains unclear. In particular, there is much disagreement about whether structural adjustment programs and democratization have helped to make patronage less pervasive in African politics. Here, I examine the case study of Uganda, which has received much praise for its large-scale economic and political reforms since the late 1980s. However, at the same time, Uganda has also experienced a near-explosion in the number of districts (the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 37 publications
2
112
1
5
Order By: Relevance
“…Yet widespread clientelism in Uganda persists, and it has facilitated the single-party government of the National Resistance Movement (NRM) led by President Museveni to retain power for nearly 30 years (van de Walle 2003(van de Walle , 2007Muhumuza 2009;Green 2010;Tripp 2010). As one recent study points out, BIn Uganda, the ruling NRM has established patronage networks throughout the country through the use of local government.…”
Section: Research Setting: the Ugandan Contextmentioning
confidence: 99%
“…Yet widespread clientelism in Uganda persists, and it has facilitated the single-party government of the National Resistance Movement (NRM) led by President Museveni to retain power for nearly 30 years (van de Walle 2003(van de Walle , 2007Muhumuza 2009;Green 2010;Tripp 2010). As one recent study points out, BIn Uganda, the ruling NRM has established patronage networks throughout the country through the use of local government.…”
Section: Research Setting: the Ugandan Contextmentioning
confidence: 99%
“…Green 2008Green , 2010Awortwi & Helmsing, 2014a) emphasizes that the driving motivations of district creation are situated at the national/regime level because the bottom line incentive relates to the urge to secure the political survival of president Museveni and the National Resistance Movement (NRM). Securing political support can be achieved in two different ways:…”
Section: District Creation Rationales: National Actor Interests Prevailmentioning
confidence: 99%
“…Scholarly research has mainly focused on the role of national actors and factors to explain the multiplication of districts (e.g. Green 2008Green , 2010Niringiye, Bbaale & Olowo, 2013;Awortwi & Helmsing, 2014a, 2014b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, studies have found that the quota policy has been used to bolster the incumbent party (Bauer 2008b;Green 2010;Muriaas and Wang 2012), in this way promoting women who are loyal to the governing party (Goetz 2003;Tripp 2006). The strong ties between the ruling party and quota representatives may further relegate the latter to take positions as subordinate or tokens (Bauer 2008a(Bauer : 362, 2008bGoetz 2003: 118).…”
Section: Tracing Gender Differences In Parliamentary Debatesmentioning
confidence: 99%